Racial/ethnic differences in the utilization of chemotherapy among stage I-III breast cancer patients, stratified by subtype: Findings from ten National Program of Cancer Registries states. (February 2019) - Zhang, Lu; King, Jessica; Wu, Xiao-Cheng; Hsieh, Mei-Chin; Chen, Vivien W.; Yu, Qingzhao; Fontham, Elizabeth; Loch, Michelle; Pollack, Lori A.; Ferguson, Tekeda
Highlights: Racial/ethnic disparities in chemotherapy (chemo) use vary by breast cancer subtypes. Hispanics with HR-/HER2- had higher odds of chemo use than non-Hispanic whites (NHW). Non-Hispanic blacks (NHB) with HR+/HER2- had higher odds of chemo use than NHW. NHB and Hispanics were more likely to receive delayed chemo, regardless of subtype. No racial/ethnic differences existed regarding the utilization of neo-adjuvant chemo. Abstract: Background: The study aimed to examine racial/ethnic differences in chemotherapy utilization by breast cancer subtype. Methods: Data on female non-Hispanic white (NHW), non-Hispanic black (NHB), and Hispanic stage I-III breast cancer patients diagnosed in 2011 were obtained from a project to enhance population-based National Program of Cancer Registry data for Comparative Effectiveness Research. Hormone receptor (HR) and human epidermal growth factor receptor 2 (HER2) were used to classify subtypes: HR+/HER2-; HR+/HER2+; HR-/HER2-; and HR-/HER2 + . We used multivariable logistic regression models to examine the association of race/ethnicity with three outcomes: chemotherapy (yes, no), neo-adjuvant chemotherapy (yes, no), and delayed chemotherapy (yes, no). Covariates included patient demographics, tumor characteristics, Charlson Comorbidity Index, other cancer treatment, and participating states/areas. Results: The study included 25, 535 patients (72.1% NHW, 13.7% NHB, and 14.2% Hispanics). NHB with HR+/HER2- (adjusted odds ratio [aOR] 1.22, 95% CI 1.04–1.42) and Hispanics with HR-/HER2- (aOR 1.62, 95% CI 1.15–2.28) were more likely to receive chemotherapy than their NHW counterparts. Both NHB and Hispanics were more likely to receive delayed chemotherapy than NHW, and the pattern was consistent across each subtype. No racial/ethnic differences were found in the receipt of neo-adjuvant chemotherapy. Conclusions: Compared to NHW with the same subtype, NHB with HR+/HER2- and Hispanics with HR-/HER2- have higher odds of using chemotherapy; however, they are more likely to receive delayed chemotherapy, regardless of subtype. Whether the increased chemotherapy use among NHB with HR+/HER2- indicates overtreatment needs further investigation. Interventions to improve the timely chemotherapy among NHB and Hispanics are warranted.